Design a model to measure the effect of interior spaces on individuals with hyperactivity and attention deficit disorder (ADHD) to develop them - Al-Towairqi, Nada Salem; Al-Sabban, Reem Farouq (Journal of Humanities & Social Sciences, 2025)
The research aims to study the internal environments that affect productivity، the ability to perform tasks، creativity and time management of individuals، through identifying the stimuli that increase some disorders such as attention deficit or hyperactivity disorder or all of them in order to understand them، and studying the behaviors that motivate the individual to develop and create a space or environment that helps him coexist with this type of disorder، taking into account the foundations of design and the psychology of materials and colors، and other factors and their impact on this category for each space in each environment (bedroom and work at home، office at the workplace). Then the research tool was designed and was in two parts; the first part: a model for the scale of disorder associated with space and its application to a sample using a survey tool to reach the results، and the second part: based on the first part، the effect of the designed environments on this sample was discussed. Previous studies were then analyzed and some health strategies (mental، sensory and behavioral) and thoughtful design solutions for the sample environments were suggested، which positively reflect on individuals، results and recommendations. These recommendations include: the necessity of studying the sample of individuals diagnosed with the disorder and knowing the physiological and psychological needs in the places where they spend most of their day. Educating designers about the importance of interior design and its foundations when designing spaces for this category through social media، for example. There may also be a lack of interest in the environment of people suffering from such disorders، so specialists in disorders must be directed، in cooperation with building officials، architects and interior designers، to intensify this interest. In addition to conducting more research and studies so that environments can be developed and supported، resulting in productivity، stress reduction، etc.
Keywords: Interior design; ADHD; Behavior (attitude); interior spaces; environments (Spaces); Design solutions; Strategies